One-Pot Synthesis of α-Fluoroketones and 3-Fluoro-2,4-diarylfurans from Trifluoromethyl β-Diketones via Decarboxylation - Shao, Tongle; Fang, Xiang; Yang, Xueyan (Synlett, 2015)
A facile and mild one-pot protocol via decarboxylation of trifluoromethyl β-diketones has been developed for the construction of α-fluoroketones and 3-fluoro-2,4-diarylfurans which are important units in many biologically active compounds and useful precursors in a variety of functional-group transformations.
Keywords: fluorine; α-fluoroketones; 3-fluorofurans; one-pot; decarboxylation